Orthopaedic heritage in seventeenth Century Dutch and Flemish genre painting - Canillas, Fernando; Menéndez, Pablo; Canillas, Marta (Springer Nature, 2025)
Purpose: The aim of this study is to explore the representation of professionals engaged in medico-surgical practices within seventeenth-century Dutch and Flemish genre painting. The research focuses on how these works of art mirror the rich diversity of healthcare practitioners, the techniques employed, the spaces of care depicted, and the societal perception of medical knowledge. Materials and methods: An extensive review has been conducted of the foremost museums and painting databases devoted to seventeenth-century Dutch and Flemish art related to the treatment of illness. Over one hundred and fifty works, created by some sixty painters active during this period, have been subjected to a meticulous formal and iconographic analysis. Results: The study unveils the coexistence of a multifaceted array of medical figures - from physicians and barber-surgeons to empirics and charlatans - and illustrates how paintings of the time portrayed urban, rural, and mercantile settings of medical practice. These visual narratives document surgical techniques, orthopaedic interventions, and the complex social dynamics between patients and healthcare providers. Furthermore, the works frequently incorporate satirical and allegorical elements that critique the pretensions of the medical elite, highlight surgical ineptitude, or expose the cunning of itinerant healers. Conclusion: Seventeenth-century genre painting serves as a vivid visual testament to the popular perception of medicine and provides invaluable insight into the tensions between academic medicine and empirical practice. These works offer a critical and nuanced lens through which to apprehend the medical culture and epistemologies of the period.